Avaliação histológica da movimentação ortodôntica em ratos diabéticos ou osteopênicos sob ação da fotobiomodulação a laser - Maia, Luiz Guilherme Martins [UNESP] (2013)
The purpose of the current study was to assess the effect of the low level laser therapy (LLLT) on the histological changes of the periodontal ligament, alveolar bone, and dentinpulp complex of teeth subjected to orthodontic movement in diabetic and osteopenic rats. Therefore, we induced diabetes and osteopenia in Wistar rats, by the administration of aloxan and by ovariectomy, respectively. Normoglycemic and non-ovariectomized animals were regarded as controls. Subsequently, the upper right first molar was submitted to mesial traction. The LLLT was carried out at 780 nm. After the sacrifice of the rats in 7, 13 and 19 days, the tissues were removed, processed and analyzed in light microscope. In both osteopenic and diabetic animals, the LLLT significantly reduced the intensity of the inflammatory response, modulated the osteoblastic/osteoclastic differentiation, and increased the blood vessels content of the periodontal ligament, as well as provided better architectural arrangement of the periodontal collagen fibers. In addition, the LLLT also attenuated the inflammation and improved vascularization in dental pulps of pulled teeth of diabetic rats, although we also observed a significant increment in the pulp collagenization. We concluded that both metabolic disturbances promoted morphological changes in the pulp and periodontal tissues during dental movement, as well as that LLLT is able to partially, but not completely, reverse the histopathological findings seen in the periodontal tissues and pulp-dentin complex.